2023
DOI: 10.3390/ijerph20105822
|View full text |Cite
|
Sign up to set email alerts
|

Avoidant/Restrictive Food Disorder (ARFID), Food Neophobia, Other Eating-Related Behaviours and Feeding Practices among Children with Autism Spectrum Disorder and in Non-Clinical Sample: A Preliminary Study

Agata Kozak,
Kamila Czepczor-Bernat,
Justyna Modrzejewska
et al.

Abstract: Previous research shows that children with autism spectrum disorder (ASD) may experience several difficulties—including those related to eating—and this area of research needs to be explored further. This study had two main objectives: (1) comparison of the clinical (autism spectrum disorder) and non-clinical sample of children in terms of avoidant/restrictive food disorder, food neophobia, other eating-related behaviours and feeding practices; (2) assessment of selected predictors of food neophobia. The final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Our research has found that a more severe caregiver pressure strategy was associated with food neophobia in children with ASD. This is consistent with previous findings [46,50].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our research has found that a more severe caregiver pressure strategy was associated with food neophobia in children with ASD. This is consistent with previous findings [46,50].…”
Section: Discussionsupporting
confidence: 94%
“…In addition to this, these children are more sensitive to these properties of food due to their sensory sensitivities and, thus, are pickier about food [45]. In addition to the fact that children with ASD are hypersensitive to stimuli that cause them to be reluctant to accept food, children with ASD may have oral motor deficits that cause constipation and diarrhea problems when they swallow food without chewing, which can lead to the refusal of this type of food [46].…”
Section: Discussionmentioning
confidence: 99%
“…Progressive research has elucidated the intricate pathways and significant roles of specific gut microbiota and the brain in regulating multiple brain functions, offering potential advancements in the understanding and management of ASD and its associated conditions, thus reinforcing the significance of continuous exploration in this complex biological domain. [2,11,[25][26][27][28][29][30] Sensory sensitivity [5 ,6, 27, 31-33] Food selectivity [4-6, 9, 10, 30, 34-55] Nutritional intake [13,14,21,[56][57][58][59][60][61][62] Diet quality [11,12,29,63,64] Nutritional status [21, [57][58][59][60][65][66][67][68][69][70][71][72][73][74][75][76] Others [2,3,6,11,15,16,19,<...…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, children diagnosed with ASD often experience motor skills challenges that can limit their participation in sports and other physical activities [ 10 , 11 , 12 ]. Additionally, selective eating preferences and sensory difficulties related to food are common in children with ASD [ 12 , 13 , 14 , 15 ]. Furthermore, specific classes of psychotropic medication are potentially implicated in obesity development among these children [ 7 , 16 ].…”
Section: Introductionmentioning
confidence: 99%